Peri-Implant Complications A Clinical Guide to Diagnosis and Treatment - Kelekis-Cholakis, Anastasia (Springer International Publishing, 2018)
This book is an up-to-date reference that provides detailed guidance on how to diagnose and manage the soft and hard tissue complications that may be associated with a functioning dental implant placement, such as peri-implant mucositis, soft tissue loss, and peri-implantitis. Treatment options for each complication are described and illustrated step by step and carefully selected cases are presented to further explain the individual stages in management and to highlight key learning points. Practical advice is offered on all aspects of diagnosis, and information is also presented on the definition and etiology of the various complications. The book is in an easy-to-read format and includes a review of the latest literature on the topic.